Research Progresses of Garnet-Type Solid Electrolytes for Developing All-Solid-State Li Batteries - Kim, Abin; Woo, Seungjun; Kang, Minseok; Park, Heetaek; Kang, Byoungwoo (Frontiers in Chemistry, 2020)
All-Solid-State Batteries (ASSBs) that use oxide-based solid electrolytes (SEs) have been considered as a promising energy-storage platform to meet an increasing demand for Li-ion batteries (LIBs) with improved energy density and superior safety. However, high interfacial resistance between particles in the composite electrode and between electrodes and the use of Li metal in the ASBS hinder their practical utilization. Here, we review recent research progress on oxide-based SEs for the ASSBs with respect to the use of Li metal. We especially focus on research progress on garnet-type solid electrolytes (Li7La3Zr2O12) because they have high ionic conductivity, good chemical stability with Li metal, and a wide electrochemical potential window. This review will also discuss Li dendritic behavior in the oxide-based SEs and its relationship with critical current density (CCD). We close with remarks on prospects of ASSB.